2017
DOI: 10.1002/jib.467
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mould microbiome and exogenous enzyme production in Moutai-flavor Daqu

Abstract: The objective of this study was to isolate and screen the mould microbiome of five Moutai‐flavor Daqu samples and to characterize and quantify the associated exogenous enzymes. In all, 11 and 18 mould genera were identified in the samples by, respectively, a culture‐dependent method and a culture‐independent high throughput sequencing method. Species of Aspergillus and Rhizopus were the dominant mould genera in the Moutai‐flavor Daqu samples. Analysis of enzyme production showed that Aspergillus versicolor in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…A previous study has shown that the contents of important esters in Baijiu are positively correlated with the numbers of LAB, indicating that a lag in fermentation and a lower ester content during Baijiu production could be caused by a lack of LAB [1]. Previous studies have shown that Staphylococcus is dominated in Daqu, with the potential to form amino acids, biogenic amines, aldehydes, free fatty acids, and esters [3,23]. The number of Staphylococcus bacteria was correlated with the biosynthesis of the main organic acids in Baijiu [24].…”
Section: Overall Structure and Diversity Of Prokaryotic Communitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study has shown that the contents of important esters in Baijiu are positively correlated with the numbers of LAB, indicating that a lag in fermentation and a lower ester content during Baijiu production could be caused by a lack of LAB [1]. Previous studies have shown that Staphylococcus is dominated in Daqu, with the potential to form amino acids, biogenic amines, aldehydes, free fatty acids, and esters [3,23]. The number of Staphylococcus bacteria was correlated with the biosynthesis of the main organic acids in Baijiu [24].…”
Section: Overall Structure and Diversity Of Prokaryotic Communitiesmentioning
confidence: 99%
“…Acetobacter, the prevalent bacteria during Baijiu production, greatly influences the flavor and taste of the final product, because it not only produces acetic acid, but also affords acetoin, a biosynthetic in Baijiu liquor [28]. Acetobacter can also select most of the acid-tolerant microbes owing to the high concentrations of acetic acid it produces [3]. In other words, Acetobacter can affect the microbial flora in the fermentation process of Baijiu, which will eventually affect the quality of the final product.…”
Section: Overall Structure and Diversity Of Prokaryotic Communitiesmentioning
confidence: 99%
See 3 more Smart Citations